Resposta :
Răspuns: 8
Explicație pas cu pas:
10³ : {123 + 34 : [(2 × 3²)² : 18 - 17⁰ × 1²⁰²⁰]} =
1000 : {123 + 34 : [(2 × 3²)² : 18 - 17⁰ × 1²⁰²⁰]} =
1000 : {123 + 34 : [(2 × 9)² : 18 - 1 × 1]} =
1000 : [123 + 34 : (18² : 18 - 1)] =
1000 : [123 + 34 : (18²⁻¹ - 1)] =
1000 : [123 + 34 : (18¹ - 1)] =
1000 : (123 + 34 : 17) =
1000 : (123 + 2) =
1000 : 125 = 8
[tex]\red{\bf \underline{Formule~pentru~puteri}:}[/tex]
[tex]\bf a^{0} = 1;[/tex]
[tex]\bf (a^{n})^{m} = a^{n \cdot m};[/tex]
[tex]\bf a^{n}\cdot a^{m} =a^{n+m};[/tex]
[tex]\bf a^{n}: a^{m} =a^{n-m}[/tex]
==pav38==
Baftă multă !